2016
DOI: 10.1177/0748233715579804
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mutagenicity and genotoxicity of indium tin oxide nanoparticles using the Ames test and micronucleus assay

Abstract: In this study, the mutagenicity and genotoxicity of indium tin oxide (ITO) nanomaterial were assessed using two standard genotoxicity assays, the Salmonella reverse mutation assay (Ames test) and the in vitro micronucleus (MN) assay. Seven different concentrations (12.5, 25, 50, 75, 100, 125, and 150 µg/plate) of this nanomaterial were tested using the Ames test on the TA98 and TA100 strains in the presence and absence of the S9 mixture. At all the concentrations tested, this substance did not significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
0
10
0
1
Order By: Relevance
“…Therefore, the validity and reliability of test results indicating a potential for genotoxic/DNA damaging effects is difficult to assess. There are indications that the effects might be secondary, most likely as a result of ROS induction (Akyıl et al, 2015;Badding et al, 2014;Cigerci et al, 2015;Lison et al, 2009;Tabei et al, 2015Tabei et al, , 2016.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, the validity and reliability of test results indicating a potential for genotoxic/DNA damaging effects is difficult to assess. There are indications that the effects might be secondary, most likely as a result of ROS induction (Akyıl et al, 2015;Badding et al, 2014;Cigerci et al, 2015;Lison et al, 2009;Tabei et al, 2015Tabei et al, , 2016.…”
Section: Discussionmentioning
confidence: 96%
“…With the exception of the Ames test (Akyıl et al, 2015), all the other studies were not performed according to validated and adopted guidelines and/or have not been described in sufficient detail to allow the assessment of their validity. Solubility in the various vehicles used was mostly not determined; this may be crucial in view of the stated poor solubility/insolubility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro, an indium compound was found to decrease cell viability, induce oxidative stress damage (Ahamed, Akhtar, Khan, Alhadlaq, & Aldalbahi, 2017; Alkahtane, 2015; Badding, Stefaniak, Fix, Cummings, & Leonard, 2014), promote DNA cleavage and increase the micronuclei frequency (Akyil, Eren, Konuk, Tepekozcan, & Saglam, 2016; Lin, Yang, Li, Chang, & Kuan, 2013). Ahamed et al have shown that IO nanocubes induce cell viability reduction and cell membrane damage in human lung epithelial (A549) cells in a dose‐ and time‐dependent manner (Ahamed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%